The role of gamified environmental interpretation in boosting destination perceived value - Ana Isabel Polo-Peña; María Lina Fernández-Ruano; Dolores María Frías-Jamilena (Tourism & Management Studies)
This study examines the effectiveness of a strategy designed to enhance destination perceived value (PV) by raising tourists’ awareness and understanding of sustainability. The approach uses information and communications technologies—specifically, gamification—to design an environmental interpretation (EI) program for tourists. While the literature has tended to approach gamification from a systemic perspective, this study addresses a significant gap by adding the experiential dimension. The research (a) designs an EI program based on a holistic gamified approach that takes game objectives, features, the context of the application, and the participant experience into consideration; (b) measures the tourist’s perspective on the design to test whether it successfully generated a motivating and enjoyable (gameful) experience that could positively impact their behaviours; and (c) determines whether a gameful EI experience positively influences destination PV. The results show that the proposed strategy contributes to enhancing destination PV. The gamification of EI experiences is thus found to be a valid strategy for enhancing destination sustainability, tourist behaviours, and, ultimately, destination competitiveness.